(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
In contemporary society human beings are facing “global” challenges that have a direct impact (which is often devastating) on collective and individual lives. Private lives are threatened by the “unintended consequences” – in the words of Ulrich Beck – of the malfunctioning of social dynamics far beyond the understanding of individuals. In the last few decades, several traumatic events (some of unprecedented scope) have made their appearance on the social scene, producing implications that are difficult to overestimate. The “catastrophic” nature of these events raises the ques- tion of the “state of health” of the “civilization process” – to put it in the terms of Norbert Elias. In the first paragraph I analyze, thanks to the theories of Anthony Giddens and Ulrich Beck, the distinguishing features of “late modernity”. In the second, I discuss the relations between the globalization process and the “civilization process” through the theoretical framework of the sociology of culture. The aim of this essay is to give a small sociological contribution to the understanding of a world that appears to be, at first glance, more and more indecipherable.